2022
DOI: 10.1021/acs.jnatprod.1c01179
|View full text |Cite
|
Sign up to set email alerts
|

Enigmazole C: A Cytotoxic Macrocyclic Lactone and Its Ring-Opened Derivatives from a New Species of Homophymia Sponge

Abstract: A new macrolide, enigmazole C ( 1 ), and two additional analogues, enigmazoles E ( 2 ) and D ( 3 ), were obtained from a new species of the Homophymia genus as part of an ongoing discovery program at PharmaMar to study cytotoxic substances from marine sources. The structures were fully characterized by cumulative analyses of NMR, IR, and MS spectra, along with density functional theory computational calculations. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…4 Photooxidation of Enigmazole B (1) and 15-OMe Enigmazole A (7). A solution of 15-OMe enigmazole A (1.0 mg, 1.6 × 10 −6 mol) in CD 3 OD (180 μL) was placed in a 3 mm NMR tube and irradiated by a flood lamp (250 W) at rt for 6 h. The reaction mixture was purified by C 18 HPLC to afford enigmimide A (5). In a similar manner, 1 was irradiated for 24 h and purified by HPLC to afford enigmimide B (4) together with cis-enigmimide B (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Photooxidation of Enigmazole B (1) and 15-OMe Enigmazole A (7). A solution of 15-OMe enigmazole A (1.0 mg, 1.6 × 10 −6 mol) in CD 3 OD (180 μL) was placed in a 3 mm NMR tube and irradiated by a flood lamp (250 W) at rt for 6 h. The reaction mixture was purified by C 18 HPLC to afford enigmimide A (5). In a similar manner, 1 was irradiated for 24 h and purified by HPLC to afford enigmimide B (4) together with cis-enigmimide B (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a previous study, we reported on three cytotoxic phosphomacrolides, enigmazole A ( 6 ), 15-OMe enigmazole A ( 7 ), and its analogues, from a Papua New Guinea marine sponge Cinachyrella enigmatica . Subsequently, enigmazoles C–E were isolated as cytotoxic components from an Indonesian Homophymia sponge . During our further study of the organic-soluble portion of an aqueous extract from C.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Trying to establish the relative configuration at C3, we followed the i J /DP4 protocol of Daranas, Sarotti et al, involving a conformational search within a 5-kcal/mol interval, and then calculated the theoretical chemical shifts at the B3LYP/6-31G(d,p) level [ 36 , 37 , 38 ]. Contrasting calculated vs. experimental chemical shifts gave rise to a better DP4 score for the (3 R *,7 S *,11 R *)-1b diastereoisomer (C/DP4: 94.25%, H/DP4: 100%).…”
Section: Resultsmentioning
confidence: 99%
“…2 Very recently, Jimeńez, Rodri ́guez, and co-workers from PharmaMar reported the isolation of additional enigmazole congeners, designated as enigmazole C−E (5−7), from a new Indonesian sponge that belongs to the Homophymia genus. 3 It was reported that (−)-enigmazole A (1) showed significant cytotoxicity against the National Cancer Institute (NCI) panel of human cancer cell lines with an average GI 50 value of 1.7 μM, albeit with essentially no selectivity among the tested cell lines. Meanwhile, (−)-enigmazole B (4) has a characteristic dihydropyran ring substituted with an α,β-unsaturated ester as an acid-, base-, and light-sensitive substructure.…”
mentioning
confidence: 99%